The portrayal of Islamic state in selected online newspapers in Malaysia: A Framing Approach / Norizzati Saifuddin and Ismail Sualman - Saifuddin, Norizzati; Sualman, Ismail (Centre for Media and Information Warfare Studies, 2017)
This study is about the portrayal of Islamic State in selected online newspaper in Malaysia using a framing approach. Malaysia has been stressed with the increasing numbers of Islamic State threats in this country. Internet penetration has made the process of radicalization and recruitment happened faster over online media. Public need to have the right information in order to reduce their participation in Islamic State through information about the Islamic State threats in online news. Media framing plays a significant role in shaping opinions and views of audiences through its portrayal. Hence, the objectives of this study are to study the theme, dominant issue, types of frame, source of news, and news slant used in Islamic State reporting in selected online newspapers in Malaysia. Using the framing approach, this study used quantitative content analysis by analysing 260 news articles from four selected online newspapers in Malaysia. It comprises of two Malay online newspapers which are hmetro. com.my and sinarharian.com.my and two English online newspapers which are malaysiakini.com and thestar.com.my. The finding revealed that the terrorism is the main theme, and counter terrorism is the dominant issue reported by online media. Thematic frame and conflict frame are highly used in portraying about Islamic State. Malaysia is the most country mentioned, and government is the main source of news. The majority of news articles also portrayed negative slant in Islamic State coverage. As a result, this study managed to prove that there are significant differences between three out of the four variables through statistical analysis.